Use of the “spaghetti” technique for surgical treatment of lentigo maligna - Gabriela Suemi Shimizu; Farid Bark Hamdar; Claudio Henrique Santana Tavares dos-Santos; Luiz Augusto Daloia Souza; Fernando Henrique Sgarbi Parro; Ivan Dunshee de Abranches Oliveira Santos; Christiane Steponavicius Sobral; Eduard René Brechtbühl (Revista Brasileira de Cirurgia Plástica, 2019)
Lentigo maligna (LM) is a melanoma in situ that commonly presents as a macula with progressive and irregularly pigmented growth, especially in the face of elderly people with sun-damaged skin. This melanoma in situ has a risk (30-50%) of progression to lentigo maligna melanoma. Complete surgical excision of the lesion requires margins of at least 10 mm, even for lesions in situ. However, when the growth of LM occurs in areas of aesthetic or functional implications (face, neck, and soles), the excision is often reduced to preserve important anatomic structures and for cosmetic purposes. Moreover, the peripheral margins may be clinically ill-defined and not always pigmented, and thus, such cases are associated with underestimated extension and risk of insufficient resection. The "spaghetti" technique, described by Gaudy Marqueste, is a strategic surgical approach based on sampling of a range of "spaghetti-like" strips to determine the margins of the lesion prior to removal of the tumor. After the pathological confirmation of neoplasia-free margins, the main central lesion is resected, allowing reconstruction of the defect in the same procedure, as an alternative to Mohs micrographic surgery.